Preservação arquivística: uma análise sobre a preservação digital nas instituições públicas brasileiras - FIGUEIREDO, Gabriel William dos Santos (2022)
The preservation of documents is any action that aims to ensure the integrity and protection of the information recorded, so that they are not lost, by the tear of the supports and to assist the procedure, tools such as software that perform digital preservation, contribute to document management and storage. The objective of the research is to make an analysis of institutions that use digital preservation software (open source), comparing the theory and practice of software in the institutions, discussing the techniques and strategies. The research problem is to obtain information about the software operation in the selected institutions, which perform digital preservation through digital repositories. The Brazilian institutions that use the software, such as DSpace, ICA-AtoM, Alfresco and SIAN, aim to store, preserve and make available the information that is stored in their collections, a procedure that is not common, especially in the Brazilian public sector. The materials and methods were divided into two stages: the first is a survey of information about digital preservation and the use of software in institutions. The second stage consisted of making a cross between the characteristics of the presented software, the institutions, and the normative instruments, identifying common elements among these tools. The universe of research is the Brazilian public institutions, which adhered to the archival methods, with a sample delimited to the state agencies, responsible for the documentary guard, formed by National Archive, Public Archive of the State of São Paulo, Federal Data Processing Service and Brazilian Institute of Information Science and Technology. The results are presented in a discussion, identifying the characteristics of the software to know if they are present in the institutions, which executed the software making a comparison, between theory and practice, with the theoretical basis of the LOCKSS systems and the e-Arq model (from Brazil), to find out if the software is in line with the tools of organization and access. The Brazilian Institute of Science and Technology Information uses the DSpace platform for the elaboration of a digital repository, the São Paulo Public Archive installed the ICA-AtoM software, the Federal Data Processing Service works with Alfresco software and the National Archive developed its own platform which is called SIAN for the management of the collection. Each of the software installed in the institutions is responsible for performing digital preservation. Through the research, it was possible to verify that the presented institutions partially meet the instruments of the e-Arq model and LOCKSS, in the execution of their activities. As final considerations, it was possible to identify that the institutions obtained satisfactory results in the collection management with the implementation of digital preservation software.